2007
DOI: 10.1029/2006jc004028
|View full text |Cite
|
Sign up to set email alerts
|

Observation and modeling of surface currents on the Grand Banks: A study of the wave effects on surface currents

Abstract: [1] We investigate the effects of surface waves on surface currents using surface drifter data from the Grand Banks and a coupled current-wave-drifter model. The theoretical basis of the study is Jenkins' theory of wave-current interaction in which wind-generated surface currents are modified by wind-wave and wave-current momentum transfers. The total surface current is the sum of the wave modified current, the Stokes drift and the tidal current. Jenkins' formulation was incorporated into the Princeton Ocean M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 58 publications
3
48
1
Order By: Relevance
“…The significance of the former and latter component in the surface currents over the Grand Banks was clearly demonstrated by Han (2005) and Tang et al (2007), respectively. In this algorithm, the eddy viscosity ν is assumed to be proportional to the surface friction velocity u * and a characteristic depth H:…”
Section: Blending Of the Satellite-and Model-derived Mean Currentsmentioning
confidence: 98%
See 4 more Smart Citations
“…The significance of the former and latter component in the surface currents over the Grand Banks was clearly demonstrated by Han (2005) and Tang et al (2007), respectively. In this algorithm, the eddy viscosity ν is assumed to be proportional to the surface friction velocity u * and a characteristic depth H:…”
Section: Blending Of the Satellite-and Model-derived Mean Currentsmentioning
confidence: 98%
“…2c. Table 5 shows that the composite and observed currents at the surface are much closer than at 15 m depth, (2003) and Tang et al (2007) found using numerical ocean models, inclusion of the Stokes drift is necessary to represent the surface current speed in this region accurately.…”
Section: Comparison With Surface Driftersmentioning
confidence: 99%
See 3 more Smart Citations